2021
DOI: 10.1017/jfm.2021.219
|View full text |Cite
|
Sign up to set email alerts
|

Modelling finger propagation in elasto-rigid channels

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 64 publications
(181 reference statements)
2
23
0
Order By: Relevance
“…2017 a , b ; Fontana et al. 2021). Those latter considerations are of primary importance for numerous biological flows (Heil & Hazel 2011), in particular in collapsed lungs (Grotberg 1994; Grotberg & Jensen 2004; Heil, Hazel & Smith 2008).…”
Section: Introductionmentioning
confidence: 99%
“…2017 a , b ; Fontana et al. 2021). Those latter considerations are of primary importance for numerous biological flows (Heil & Hazel 2011), in particular in collapsed lungs (Grotberg 1994; Grotberg & Jensen 2004; Heil, Hazel & Smith 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A modelling framework for fluid–structure interaction flows was proposed by Fontana et al. (2021), based on a depth-averaged model to describe the propagation of an air finger into a collapsed elasto-rigid channel. They showed that the presence of the elastic wall can lead to interaction between solution branches that are isolated in the rigid channel, thus altering their stability and potentially leading to complex dynamics at higher levels of initial collapse.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we enable the simulation of intricate interfacial patterns by extending the depth-averaged model introduced by Fontana et al. (2021) to include an artificial disjoining pressure to prevent self-intersection of the interface. We investigate systematically the transition to feathered modes across a range of levels of collapse.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this experiment, numerous studies have been performed to generate further insight into how the taper angle influences viscous fingering [2,3,14,73,86,99]. Other popular physical alterations to the Hele-Shaw cell include uniformly separating the plates in time [43,44,83,100,122,133,143], rotating the entire Hele-Shaw cell at a given angular velocity [5,17,43,119], or replacing one of the plates with an elastic membrane [1,32,48,85,89,[108][109][110][111]. All of these configurations have been shown to produce patterns distinct from traditional Saffman-Taylor fingering.…”
Section: Introductionmentioning
confidence: 99%